The Impact of LATCH Score-Based Education on Latch Accuracy in Primigravida Mothers - Heni Setyowati; Haryono Haryono; Oktia Woro Kasmini Handayani; Evi Widowati (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: Improper infant positioning and attachment during breastfeeding is a common problem among mothers, mainly due to a lack of knowledge about breastfeeding techniques. This lack of understanding regarding correct breastfeeding technique contributes to nipple fissures and breast engorgement, ultimately impacting infant nutrition. This study aimed to assess how LATCH-based education method influences the proper latching of breastfeeding mothers in Magelang City Methods: This study employed a quasi-experimental pre-post design conducted in Magelang City. The participants were breastfeeding mothers who were doing it for the first time. A total of 44 participants were enrolled as samples through purposive sampling. The tools used included a questionnaire and an evaluation observation sheet to gauge the effectiveness of breastfeeding techniques. The data analysis was performed using the Wilcoxon Signed-Rank Test. Results: The results showed that three respondents had good attachment accuracy (6.8%), 38 mothers had sufficient latch (86.6%), and 3 had inadequate latch (6.8%). After receiving education, 32 respondents (72.7%) had a good latch, while 12 respondents (27.3%) had a sufficient latch. Respondents who achieved LATCH-Score indicators increased, including LATCH-on, audible swallowing comfort, and hold with a total increase of respondents of 5 (12%), 24 (76%), 20 (46%), and 15 (34%), respectively. There was a significant relationship between latch accuracy before and after being given education about breastfeeding techniques in primigravida breastfeeding mothers in the Magelang City area (P value= 0.000). Conclusion: Latch score-based breastfeeding education on breastfeeding techniques affects how well new mothers attach their infants during breastfeeding. It is potentially used to support successful breastfeeding.